FACILITIES MANAGEMENT AT GURUH GEMURAI WATERFALL TOURISM, KUANTAN SINGINGI PROVINCE RIAU - Liza Elwida; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This study aims to determine the management of facilities at the tourist attraction of the Guruh Gemurai Waterfall, Kuantan Singing Regency, Riau Province. Elements of organizing, implementing and monitoring management. And loading facilities, Food and Beverage, Support Industries. This study uses a qualitative method with a qualitative descriptive approach to describe and explain the circumstances that occur by collecting data and information in the field. The key informants in this study are the Head of Tourism, Tourism Object Managers and Visitors. In this study, the data collection techniques used were interviews, observation and documentation. Based on the results of the study, it can be concluded that the conditions of the facilities available at the Guruh Gemurai Waterfall Tourism Object are sufficient, however, there are several facilities that are not optimally maintained due to lack of managed facilities and lack of maintenance related to cleanliness from the manager such as toilets, changing rooms, parks and gazebos. . Keywords: management, Facility, Guruh Gemurai Waterfall Tourism Object